The future of accommodation offers: A perspective from an established Alpine destination - Volgger, Michael; Pechlaner, H.; Lun, L.; Prukker-Losonczi, B. (2016)
Established accommodation providers in traditional tourism destinations feel increasing pressure both internally, by new accommodation offers such as Airbnb, and externally, by providers in emerging tourist destinations. The paper presents some findings from an exploratory study on how accommodation providers in the developed, rural, and mainly leisure oriented tourism destination of South Tyrol (Italian Alps) perceive their future in terms of challenges and opportunities. Based on a mixed method design that combines quantitative data with qualitative interviews, the study explores emerging landscapes of accommodation offers from the perspective of providers.